Tradisi Meeparika Menanam Padi pada Masyarakat Desa Mata Kecamatan Kambowa Kabupaten Buton Utara - Syarif; Wa Kuasa Baka; Arie Toursino Hadi (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
This study investigates the Meparika rice planting tradition in Mata Village, aiming to explore its process and inherent meanings. A descriptive qualitative method was employed to delve into the execution and symbolism of this tradition. The findings reveal that Meparika transcends mere farming techniques, reinforcing community solidarity and cultural identity in Mata Village. These insights contribute to understanding traditional practices and cultural preservation.